2020
DOI: 10.2478/sgem-2019-0050
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the soil constitutive models on the seismic analysis of pile-supported wharf structures with batter piles in cut-slope rock dike

Abstract: AbstractIn coastal regions, earthquakes caused severe damage to marine structures. Many researchers have conducted numerical investigations in order to understand the dynamic behavior of these structures. The most frequently used model in numerical calculations of soil is the linear-elastic perfectly plastic model with a Mohr-Coulomb failure criterion (MC model). It is recommended to use this model to represent a first-order approximation of soil behavior. Therefore, it is nece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 43 publications
(98 reference statements)
0
2
0
Order By: Relevance
“…Su et al [17] conducted a refined Three-Dimensional (3D) Finite Element (FE) model, including the refined modeling of free-field boundaries and soil-pile interaction, and the seismic performance of the wharf-ground system was systematically explored. Deghoul et al [18] proposed three soil constitutive models: a linear-elastic perfectly plastic model (MC model), an elastoplastic model with isotropic hardening (HS model), and the Hardening Soil model with an extension to the small-strain stiffness (HSS model) with different accuracy to study the behavior of a pile-supported wharf embedded in a rock dike. Meng et al [19] noted that the peak acceleration, spectral characteristics, and ground vibration input direction significantly affected the seismic demand of each performance index by analyzing the critical dynamic response characteristics of piled wharfs under earthquake action.…”
Section: Introductionmentioning
confidence: 99%
“…Su et al [17] conducted a refined Three-Dimensional (3D) Finite Element (FE) model, including the refined modeling of free-field boundaries and soil-pile interaction, and the seismic performance of the wharf-ground system was systematically explored. Deghoul et al [18] proposed three soil constitutive models: a linear-elastic perfectly plastic model (MC model), an elastoplastic model with isotropic hardening (HS model), and the Hardening Soil model with an extension to the small-strain stiffness (HSS model) with different accuracy to study the behavior of a pile-supported wharf embedded in a rock dike. Meng et al [19] noted that the peak acceleration, spectral characteristics, and ground vibration input direction significantly affected the seismic demand of each performance index by analyzing the critical dynamic response characteristics of piled wharfs under earthquake action.…”
Section: Introductionmentioning
confidence: 99%
“…The soil is complex in nature and highly variable and is extremely susceptible to external factors such as environment and weather. It was found that there are 3% of accidents caused by design errors [1,2]. Instead, the soil itself is the cause of accidents in geotechinical engineering.…”
Section: Introductionmentioning
confidence: 99%